Struktur Gerak Tari Sayak di Desa Air Batu Kecamatan Ranah Pemberap Kabupaten Merangin Provinsi Jambi - Putri S Mulyadi; Herlinda Mansyur (Imajinasi : Jurnal Ilmu Pengetahuan, Seni, dan Teknologi, 2024)
The purpose of this study is to explain and describe the movement structure of Sayak Dance in Air Batu Village, Ranah Pemberap District, Merangin Regency, Jambi Province. This type of research is qualitative research with descriptive methods. Research instruments are researchers themselves and assisted by supporting instruments such as stationery and cameras. Data was collected through observation, interviews, and documentation. The steps of analyzing data are data collection, data reduction, data presentation and conclusions. The results showed that the relationship of basic elements, Sayak Dance has basic elements related to the attitude of the movement of body parts, starting from the head, body, hands, feet. The attitudes and movements contained in the Sayak Dance consist of: 1) attitudes and movements seen in a) the attitude of the head is upright, upright motion on the head does not exist. 2) Posture and gestures are seen in: a) upright, upright and leaning forward posture b) Motion on the body is absent 3) Posture and hand gestures are seen in: a) attitude on the hand lift sambah b) motion on the hand open straight sambah, open right sambah, pat me up, pat the right side of the leaf, pat the bottom slap, pat the back 4) attitude and motion on the feet seen in: a) attitude of the right foot, squat, middle stance, right lift, lift left, and bend. The grammatical hierarchical relationship system contained in Sayak Dance consists of 15 motifs, 8 phrases, 4 sentences and 1 cluster. Sayak dance includes syntagmatic relationships, relationships that are like links that cannot be separated or exchanged between the sati and others.